Pengaruh Fenol dan Saponin pada Madu Hutan Apis Dorsata dan molekul docking pada penanda preeklampsia - yusari; Soetrisno; Prayitno, Adi; Wasita, Brian (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2024)
Molecular docking is an important computational method for drug design. It can be used to predict receptor binding interactions with ligans. In addition, phenol-derived compounds and Saponins are also reported to have various activities such as anti-hypertensive, anti-inflammatory and anti-apoptosis agents. The purpose of this study is to predict whether the Phenol and Saponin compounds are active as anti-inflammatory agents and also to ensure that the binding interactions are stable before and after the docking calculations. The protocol is carried out in accordance with the standards set by the LPPT-UGM Testing Laboratory. The tools, programs, and applications used in this study were Lenovo IdeaPad Flex 5 Processor, AMD Ryzen 5000 Series 5, AutoDock Tools (v1.5.6), Biovia Discovery Studio, AutodockVina, Swiss ADME, VegaZZ, Pubchem, and the and the pkCSM web server (http://biosig.unimelb.edu.au/pkcsm/). Trans-ADFH three-dimensional structure, as a test compound, and Prednisolone, as a standard compound, were downloaded from https://pubchem.ncbi.nlm.nih.gov/. The phytochemical analysis of ADFH includes phenol and saponin. Structure of PlGF 3D (IRV6) and VEGF (4KZN). Identification of ligands and proteins prepared using Pubchem results of molecular docking between preeclampsia through examination of PlGF and VEGF with phenols and saponins Identification of protein ligands using Pubchem, i.e., PlGF (IRV6) with phenol produced 2 interactions and 2 amino acid residues, while saponins produced 2 interactions and 6 residues. pharmacokinetics and toxicity using Swiss ADME, i.e., phenol and saponins are non-mutagenic to bacteria; the maximum safe dose for humans is 0.54 log mg/kg/day; it does not cause toxicity to the heart; the estimated dose for animals is 2.471 mol/kg; it does not cause allergies; it does not cause liver damage; a dose of 0.288 logμ/L can inhibit the growth of 50% of the protozoa T. Pyformis. The content of phenols and saponins in Apis Dorsata forest honey has a high docking score from the original ligand. Molecular docking on phenols and saponins identified PlGF with scores of -2.85, -2.85, and -2.85 kcal/mol, while saponins have +2.84, +2.29, and +2.29 kcal/mol values, which are stated to be better results than the original ligands. This means that phenol has a role as a standard drug that can have an effect on lowering PlGF levels for people with preeclampsia. Molecular docking on VEGF identified phenol with scores of -2.88, -2.88, and -2.88 kcal/mol, and saponins have +1.36, +3.46, and +1.36 kcal/mol values, which are stated to have better results than the original ligands. This means that saponins have a role as a standard drug that can have an effect on increasing VEGF levels for people with preeclampsia.